Small Interfering RNA Targeted to ASPP2 Promotes Progression of Experimental Proliferative Vitreoretinopathy - Xiao-Li Chen; Yu-Jing Bai; Qin-Rui Hu; Shan-Shan Li; Lv-Zhen Huang; Xiao-Xin Li (Mediators of Inflammation)
Background. Epithelial-mesenchymal transition (EMT) of retinal pigment epithelium (RPE) is vital in proliferative vitreoretinopathy (PVR) development. Apoptosis-stimulating proteins of p53 (ASPP2) have recently been reported to participate in EMT. However, the role of ASPP2 in PVR pathogenesis has not been identified. Methods. Immunohistochemistry was used to investigate the expression of ASPP2 in epiretinal membranes of PVR patients. ARPE-19 cells were transfected with ASPP2-siRNA, followed with measurement of cell cytotoxicity, proliferation, and migration ability. EMT markers and related inflammatory and fibrosis cytokines were measured by western blot or flow cytometry. Additionally, PVR rat models were induced by intravitreal injection of ARPE-19 cells transfected with ASPP2-siRNA and evaluated accordingly. Results. Immunofluorescence analysis revealed less intense expression of ASPP2 in PVR membranes. ASPP2 knockdown facilitated the proliferation and migration of RPE cells and enhanced the expression of mesenchymal markers such as alpha smooth muscle actin, fibronectin, and ZEB1. Meanwhile, ASPP2-siRNA increased EMT-related and inflammatory cytokines, including TGF-β, CTGF, VEGF, TNF-α, and interleukins. PVR severities were more pronounced in the rat models with ASPP2-siRNA treatment. Conclusions. ASPP2 knockdown promoted EMT of ARPE-19 cells in vitro and exacerbated the progression of experimental PVR in vivo, possibly via inflammatory and fibrosis cytokines.